The Role of Business Incubators in Generating Profits for Youth Groups - Fara Shaliza; Nurul Hasanah (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2023)
Youth play a strategic role in national economic development because their creativity, innovation, and energy can drive the growth of micro, small, and medium enterprises (MSMEs) at both local and national levels. However, many youth groups face challenges in developing their businesses due to limited capital, managerial knowledge, marketing skills, and restricted networking opportunities, which hinder optimal profit generation. Business incubators provide a strategic solution to empower youth groups by offering mentorship, training, and facilities to expand networking and access to capital, enabling sustainable profit generation. This community service program was implemented by creating a business incubator for youth groups, including business management training, marketing strategies, financial management, and direct field mentoring. The results indicate improvements in managerial skills, business productivity, and actual profit generation, along with enhanced marketing networks and digital technology utilization to broaden market reach. The conclusion emphasizes that business incubators serve as an effective mechanism to create independent, productive youth entrepreneurs who contribute meaningfully to local and national economic growth.